2018
DOI: 10.1080/09638288.2018.1503737
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of interventions targeting physical activity and/or sedentary behaviour in people with Multiple Sclerosis: a systematic review

Abstract: Background: Remaining physically active is important to maintain functional ability and reduce the incidence of co-morbidities in people with Multiple Sclerosis. The aim of this review was to evaluate the effectiveness of interventions on physical activity or sedentary behaviour in people with Multiple Sclerosis. Methods: A systematic search was conducted in May 2018 of the following databases: Web of Science Core Collections, Embase and Medline. Included studies were randomised controlled trials involving peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 72 publications
(482 reference statements)
0
27
0
Order By: Relevance
“…We speculate that PA assessed with other tools such as accelerometers and pedometers might demonstrate different relationships with BMI compared with leisure-time PA in the MS population. Additionally, there seems to be a discrepancy between objectively vs. subjectively assessed PA in PwMS [24]. Moreover, in a recent validation study of the GLTEQ, it was found that the GLTEQ scores primarily reflect moderate-to-vigorous PA rather than light PA and sedentary behavior in PwMS [25].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that PA assessed with other tools such as accelerometers and pedometers might demonstrate different relationships with BMI compared with leisure-time PA in the MS population. Additionally, there seems to be a discrepancy between objectively vs. subjectively assessed PA in PwMS [24]. Moreover, in a recent validation study of the GLTEQ, it was found that the GLTEQ scores primarily reflect moderate-to-vigorous PA rather than light PA and sedentary behavior in PwMS [25].…”
Section: Discussionmentioning
confidence: 99%
“…Focal review of interventions delivering the exercise guidelines has not been undertaken; this is fundamental to the clinical promotion of these guidelines. We will compare previous literature on exercise training safety in MS [35][36][37], and with our planned review of retention rates, intervention adherence rates, and intervention compliance rates, we will confirm recent meta-analyses [40]. Our protocol provides a systematic and robust approach to determining the safety of exercise training in a clinical population and has high utility for repetition in other clinical populations such as stroke, Parkinson's disease, and other populations where exercise prescription is a management strategy.…”
Section: Discussionmentioning
confidence: 79%
“…Relapse risk, adverse events (AE), and serious adverse events (SAE) [33,34] indicate the construct of safety in MS clinical study, and we describe these terms in Table 1. To date, only three reviews have considered the safety of exercise training for MS [35][36][37]. The most comprehensive included 26 RCTs published up until November 2013 [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are very few interventions targeting sedentary behaviour in MS, and a recent review reported that there was no evidence that physical activity interventions changed sedentary behaviour in MS 13. This is not surprising as the interventions were not specifically designed to change sedentary behaviour.…”
Section: Introductionmentioning
confidence: 99%